The The Relationship between Family Support And Quality of Life in Elderly with Dementia - Juventus Sandy D.U. Deta; Teguh Santoso (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND : The growing number of elderly individuals can result in a decline in physical and mental functioning, which in turn affects the quality of life of the elderly. The family serves as the primary support system for the elderly in maintaining their health. Effective family support can enhance the quality of life of the elderly, enabling them to enjoy a fulfilling life in their later years. OBJECTIVE: to determine the relationship between family support and quality of life in elderly people with dementia. METHOD : This is a quantitative-correlative study design with a cross-sectional design. The analysis test used is chi-square. A total of 73 respondents were sampled for the purposes of data collection. This was achieved by administering two questionnaires: one pertaining to family support and the other to quality of life (Short Form 12). RESULT : The results of this study indicate that the majority of elderly individuals aged 60–74 (69.9%), females (53.4%), reside in the same household as their children (53.4%), work as farm laborers (69.9%), have basic education (72.6%), and have moderate levels of dementia. (50.7%). Having family support shows the moderate category (91.8%), while the quality of life is mostly good (58.9%), with a significance p-value of 0.033. CONCLUSION : There is a significant relationship between family support and quality of life in elderly people with dementia.